2018
DOI: 10.1093/ehjqcco/qcy020
|View full text |Cite
|
Sign up to set email alerts
|

Admission macrophage migration inhibitory factor predicts long-term prognosis in patients with ST-elevation myocardial infarction

Abstract: STEMI patients with high admission MIF level experienced a poorer recovery of cardiac function and worse long-term adverse outcomes. Combination of Nt-proBNP with MIF further improves prognostic capability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…Prior clinical and experimental studies have shown that resistin may promote the inflammatory process via upregulating the expression of proinflammatory cytokines, including TNF-α, interleukin-6, and monocyte chemoattractant protein-1 [5,22]. TNF-α and MIF levels upon admission all participate in the process of IRI [19,23,24], and our present research indicated for the first time that resistin at admission correlated positively with them in STEMI patients. In addition to inflammation, previous studies revealed that oxidative stress also contributed to IRI via reactive oxygen species (ROS) [20,21,25].…”
Section: Discussionsupporting
confidence: 66%
“…Prior clinical and experimental studies have shown that resistin may promote the inflammatory process via upregulating the expression of proinflammatory cytokines, including TNF-α, interleukin-6, and monocyte chemoattractant protein-1 [5,22]. TNF-α and MIF levels upon admission all participate in the process of IRI [19,23,24], and our present research indicated for the first time that resistin at admission correlated positively with them in STEMI patients. In addition to inflammation, previous studies revealed that oxidative stress also contributed to IRI via reactive oxygen species (ROS) [20,21,25].…”
Section: Discussionsupporting
confidence: 66%
“…One strategy might be to specifically target the MIF/CXCR2 interface which is atheropromoting and largely detrimental in the myocardium during an ischaemic insult. Both antibodies and peptide-based compounds such as stabilized derivatives of MIF [47][48][49][50][51][52][53][54][55][56] could potentially qualify as MIF/CXCR2-specific agents. Similarly, inhibitor strategies specifically targeting the MIF/CXCR4 interaction could be envisioned, although great caution would need to be taken to spare the various protective activities of CXCR4 in the atherogenic vasculature and the ischaemic-stressed heart.…”
Section: Resultsmentioning
confidence: 99%
“…18,19,49,50 Moreover, MIF plasma levels were found to be elevated in a high proportion of ST-elevation myocardial infarction (STEMI) patients, were suggested to be an early marker of acute STEMI, and STEMI patients with high admission MIF level experienced a poorer recovery of cardiac function and worse long-term adverse outcomes. 19,[51][52][53] Moreover, the role of MIF in myocardial ischaemia/reperfusion injury (MI/RI) has become apparent from clinical studies in cardiac surgery patients and mouse models. The cardiac surgery procedure recapitulates the ischaemic and reperfusion stress seen in myocardial infarction patients, but in contrast to the endogenously occurring myocardial infarction pathology in STEMI patients subjected to percutaneous coronary intervention, the onset of inflammation and oxidative injury in cardiac surgical patients is predictable as cardiac surgery with the cardioplegia-induced myocardial arrest, assistance of cardiopulmonary bypass and the following myocardial reperfusion, reproducibly elicits an ischaemia-reperfusion sequelae.…”
Section: Mif Is a Chemokine-like Inflammatory Mediator That Promotes mentioning
confidence: 99%
“…Authors have found positive correlation between the MIF level and MI size, heart chambers and negative relation to LVEF at 3 rd day and 3 rd month after index event. Therefore, elevated levels of MIF become independent predictor of multiple coronary artery stenosis and presence of vulnerable plaque in patients with acute coronary syndrome [27] . In this way, positive correlation between MIF and number of circulating leucocyte in peripheral blood that was established in our study clarifies that late inflammatory response can be important modulator of adverse cardiac remodeling in STEMI even after successful PCI.…”
Section: Discussionmentioning
confidence: 99%